KEANEKARAGAMAN HASIL TANGKAPAN JARING INSANG (GILLNET) DI SUNGAI KEHIDUPAN DESA LUBUK RUSO KABUPATEN BATANGHARI - Ramadhan Putra, Agung; Heltria, Septy; Nelwida, (Jurnal Perikanan Pantura (JPP), 2026)
Gillnet fishing gear is a passive fishing gear in the form of a net installed in waters designed to trap fish based on their body size that is caught in the gills or other parts of the fish's body. The purpose of this study was to determine the diversity of gillnet catches in the River of Life, Lubuk Ruso Village, Batanghari Regency. The method used in this study was a survey method with sampling using a purposive sampling method. Samples taken for data were 2 gillnet fishing gears with a mesh size of 1 ¼ and carried out for 15 trips. Data analysis was carried out descriptively quantitatively with the formula of species composition, evenness index, diversity index, and dominance index. The results showed that the total gillnet catch in the River of Life, Lubuk Ruso Village consisted of 15 species. With a total catch of 1803 fish weighing 125.057 kg. The amount of the main gillnet catch was higher at 73.5% compared to the bycatch of 26.2%, and the discarded catch of 0.3%. The composition of the most caught fish species was the sebarau fish at 31.9% and the lowest was the janitor fish at only 0.3%. The diversity index value (H') obtained was 2.02, which is included in the medium category, the uniformity index value (E) was 0.75, which is included in the high category, and the dominance index value (C) was 0.18, which is included in the low category.